The roles of project stakeholders in EPCM BIM-enabled projects - Lee, C.; Chong, Heap Yih; Wang, X. (2017)
© 2017 IEEE. As Building Information Modelling (BIM) becomes prominent in the construction industry, many contract protocols have been developed to facilitate the implementation of BIM. However, most of the protocols have been developed to accommodate procurement methods such as the traditional and design and build project delivery system. None of the protocols is developed to facilitate the BIM implementation in Engineering, Procurement, and Construction Management (EPCM) project delivery system, which is one of the common procurement systems in mineral, resources and infrastructure projects. The aim of this paper is to clarify the roles of the project stakeholders in EPCM BIM-enabled projects. A comparative analysis was conducted on the CIOB Complex Projects, CIC BIM Protocol and ConsensusDocs 301 to simulate the roles of EPCM project stakeholders. The study reveals the new roles of EPCM consultants. This review is important as it provides clarity and significant insights for managing project stakeholders involved in EPCM BIM-enabled projects.